Research and development in intelligent systems XXXIII : incorporating applications and innovations in intelligent systems XXIV : proceedings of AI-2016, the Thirty-Sixth SGAI International Conference on Innovative Techniques and Applications of Artificial Intelligence /: incorporating applications and innovations in intelligent systems XXIV : proceedings of AI-2016, the Thirty-Sixth SGAI International Conference on Innovative Techniques and Applications of Artificial Intelligence. (2016) - Unknown
No abstract available